Analysis of the operation and management of Chinese new energy vehicle companies listed on the U.S. stock market: Take Li Auto as an example - Li, Nianzhang; Wang, Jiayi; Zhang, Mengran; Zhu, Mingjie; Xu, Zihan (International Journal of Global Economics and Management, 2024)
Achieving green growth is the main trend of today’s world economic development, and new energy vehicles, as the future of green energy development, are of great significance for the implementation of industrial upgrading and adjustment and the development of low-carbon economy. Based on the analysis and SWOT analysis of the financing of this enterprise, this paper puts forward reasonable development suggestions for Li Auto, a new energy vehicle company listed in the United States as an example, and provides a certain reference for such new energy vehicle companies to effectively participate in international development.